1977
DOI: 10.1021/bi00624a005
|View full text |Cite
|
Sign up to set email alerts
|

Fluidity of the lipids next to the acetylcholine receptor protein of Torpedo membrane fragments. Use of amphiphilic reversible spin-labels

Abstract: Choline esters of spin-labeled fatty acids (long-chain acylcholines) were used to probe the hydrophobic environment of the acetylcholine receptor protein in membrane fragments from Torpedo marmorata. These spin-labels competitively inhibit the binding of [3H]acetylcholine to the receptor site. Their inhibition constants (KI) were close to 200 nM. At the high membrane concentration required for electron spin resonance (ESR) experiments, the apparent inhibition constants (KIapp) differed from KI determined by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Indeed, in spite of the possible occurrence of a fluid hydrophobic phase in the vicinity of the acetylcholine receptor site [71], the receptor molecules appear strongly immobilized in the subsynaptic membrane both in vitvo [72] and in vivo [47,, suggesting the existence of protein-protein interactions. Moreover, a binding site for local anesthetics is present in the receptor-rich membrane fragments where it modulates the binding properties of the acetylcholine site (for a review, see [2]).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in spite of the possible occurrence of a fluid hydrophobic phase in the vicinity of the acetylcholine receptor site [71], the receptor molecules appear strongly immobilized in the subsynaptic membrane both in vitvo [72] and in vivo [47,, suggesting the existence of protein-protein interactions. Moreover, a binding site for local anesthetics is present in the receptor-rich membrane fragments where it modulates the binding properties of the acetylcholine site (for a review, see [2]).…”
Section: Discussionmentioning
confidence: 99%
“…Our approach to the problem has been to artificially link the spin-labeled fatty acids to intrinsic proteins in native membranes (Devaux et al. 1975;Bienvenue et al. 1977).…”
Section: Mobility Of the Hydrocarbon Chains In Direct Contact With Rhmentioning
confidence: 99%
“…However, in this latter case the apparent correlation time describing the motion is increased by more than two orders of magnitude, showing that lipid-depleted membranes cannot be used to characterize the viscosity of the boundary layer of native membranes. N M R and rod outer segment membranes, Brown et al (1977) concluded that, although the segmental motion of hydrocarbon chains was affected by the proximity of the proteins, all phospholipids can diffuse rapidly in the plane of the membrane and that boundary and free lipids exchange rapidly.Concurrently, using spin-labeled fatty acid derivatives containing specific polar head groups, we were able to explore the hydrophobic environment of different membrane-bound proteins in native membranes (Devaux et al, 1975;Lauquin et al, 1977;Bienvenue et al, 1977). Our general conclusion was that, although evidence of hindrance in the motion of spin-labeled chains accompanies the binding to the proteins, fluidity can be found in the direct environment of such proteins.…”
mentioning
confidence: 99%
“…Concurrently we used spin-labeled acyl derivatives of specific ligands or covalently bound spin-labeled fatty acids. We demonstrated the possibility that spin labels that are in direct contact with intrinsic proteins, such as the ADP carrier in mitochondria (12,13), the acetylcholine receptor in torpedo membranes (14), or rhodopsin in disc membrane fragments (15), are moving rapidly. We showed that a spin-labeled fatty acid can be anchored to rhodopsin, provided the fatty acid contains a maleimide residue linked to the carboxylic terminal.…”
mentioning
confidence: 99%